Vietnam : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This report analyzes the Comprehensive Poverty Reduction and Growth Strategy (CPRGS), the poverty reduction strategy paper of Vietnam. It evaluates the CPRGS in the international context and the national situation, economic growth in individual sectors, and social achievements in poverty reduction. It analyzes the policy implementation, macroeconomic stability, administration reforms, modern governance, and challenges and measures in poverty reduction and growth. It provides details of strategy implementation and the monitoring and evaluating system.